Two sides of the coin (Agents or stewards) - Asif Khan, Muhamad; Ur Rheman, Ramiz; Akram Nassed, Muhamad; Alharti, Mahed (Revista de la Universidad del Zulia, 2019)
ABSTRACTThe purpose of this paper is to empirically explore that in practice CEOs are agents or stewards in context of Pakistan. To test the hypothesized model, board size, board independence, CEO duality and tenure, are taken as explanatory variables to study the stated hypothesis under agency and stewardship perspective. Fixed effect panel analysis is employed to test the stated hypothesis. The hypotheses related to board andCEOattributes are formed. Findings suggest that stewardship perspective is on weaker side as compared to agency perspective in Pakistan’s corporate sector. Results of this study lack generalizability due to its unique setting and lower disclosure sources. This study contributes to the scarce literature available for developing countries as compared to the developed economies as data availability for the variables specifically CEO related characteristics is a major problem. In this context, this study data is the first to explore the insights under two competitive theories.Key words: CEO, Firm Performance, Stewardship Theory, Developing Country